Assessing displays for supporting strategic emergency management. Issue 5 (2nd November 2015) - Huggins, Thomas J.; Hill, Stephen R; Peace, Robin; Johnston, David M.
Abstract : Purpose: – Emergency management groups aiming to address community resilience work with complex systems which consist of multiple interacting dynamics. The purpose of this paper is to help ensure that information is displayed in a way which supports strategic performance, to address longer term challenges faced by these groups. Design/methodology/approach: – Ten professional emergency managers completed an online simulation of complex, community resilience related tasks faced in their normal working lives. They responded to either table-or diagram-based information about a relevant emergency management strategy. Responses were rated by academic and practitioner experts using 0-5 point Likert scales. Findings: – Analyses of the expert ratings found that certain components of macrocognitive performance reached large degrees of inter-rater reliability ( ρ =0.76, p =0.003; ρ =0.58, p =0.03; ρ =0.53, p =0.05). Current situation awareness increased by an average of 29 per cent in the diagram condition. Prospective amendment quality also increased, by an average of 38 per cent. A small sample size meant that these increases are difficult to generalise. Research limitations/implications: – Extensions of this pilot research could use larger samples and more generic simulation conditions, to increase confidence in the claim that certain displays help improve strategic emergency management planning. Practical implications: – It is recommended that further research continues to focus on current and prospective situational awareness, as measures of strategic emergency management performance which can be reliably expert rated. Originality/value: – This research provides novel methodological considerations for supporting a more strategic approach to emergency management, with a focus on longer term implications.